1969
DOI: 10.1111/j.1600-0609.1969.tb01838.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Testosterone on Erythropoiesis

Abstract: The erythropoietic effect of testosterone cyclopentylpropionate (TCP) was studied in normal, plethoric, nephreetomized and ureter‐ligated rats. The results of this study support the contention that TCP exerts its erythropoietic effect though the kidney by increasing REF production; thereby potentiating this organ to generate greater amounts of erythropoietin (EP) in response to normal and cobalt‐stimulated erythropoietic challenges. From the data, it is further concluded that TCP neither exerts a direct EP‐lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Due to the association between storage hemolysis and female menopausal status, several hypotheses attribute hemolysis to the action of sex hormones [261, 266]. Testosterone has been shown to promote erythropoiesis [268], which could explain the increased hematocrit and hemoglobin levels observed in male donors compared to female donors [269]. Alternatively, it has been suggested that monthly blood loss in premenopausal female donors results in a younger population of circulating RBCs, which are less susceptible to stress and hemolysis during storage [267].…”
Section: Overview: Quality Assessment Of Stored Red Cell Concentratesmentioning
confidence: 99%
“…Due to the association between storage hemolysis and female menopausal status, several hypotheses attribute hemolysis to the action of sex hormones [261, 266]. Testosterone has been shown to promote erythropoiesis [268], which could explain the increased hematocrit and hemoglobin levels observed in male donors compared to female donors [269]. Alternatively, it has been suggested that monthly blood loss in premenopausal female donors results in a younger population of circulating RBCs, which are less susceptible to stress and hemolysis during storage [267].…”
Section: Overview: Quality Assessment Of Stored Red Cell Concentratesmentioning
confidence: 99%
“…Testosterone replacement is associated with an increase in red cell mass presumably through its effects on erythropoietin and stem cell proliferation (Fried et al, 1966;Naets and Wittek, 1968;Rencricca et al, 1969). Therefore, testosterone replacement should not be administered to men with baseline hematocrit of 52% or greater without appropriate evaluation and treatment of erythrocytosis ( Table 4).…”
Section: Erythrocytosismentioning
confidence: 99%